The Effect Of Principal Academic Supervision And Teacher Performance On Student Learning Outcomes In Elementary Schools In South Kotamobagu District, Kotamobagu City - Wiwin Herswinda Mamonto; Meisie L. Mangantes; Widdy H. F. Rorimpandey (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to analyze the effect of principal academic supervision and teacher performance on student learning outcomes in elementary schools in South Kotamobagu District, Kotamobagu City. This study employed a quantitative approach using an ex post facto method, as the variables were observed based on existing conditions without any experimental treatment. The population consisted of teachers and students, with samples including teachers and fifth-grade students selected through purposive sampling technique. Data were collected through questionnaires, observation, and documentation. Questionnaires were used to measure principal academic supervision and teacher performance, observation was conducted to support data related to the learning process, while documentation was used to obtain student learning outcomes data. The collected data were analyzed using simple linear regression and multiple linear regression techniques. Prior to hypothesis testing, prerequisite tests were conducted, including normality, linearity, and multicollinearity tests to ensure the appropriateness of the data. The results of the analysis indicate that principal academic supervision has a positive and significant effect on student learning outcomes with a significance value of 0.004 < 0.05. Teacher performance also shows a positive and significant effect on student learning outcomes with a significance value of 0.000 < 0.05. Furthermore, simultaneously, principal academic supervision and teacher performance have a significant effect on student learning outcomes with a significance value of 0.000 < 0.05. These findings indicate an interrelated relationship between academic supervision, teacher performance, and student learning outcomes in the learning process at the elementary school level. Keywords: academic supervision, teacher performance, learning outcomes